(68)Ga-NOTA-CHSg and (99m)Tc-CHSg Labeled Microspheres for Lung Perfusion and Liver Radiomicrospheres Therapy Planning - Amor-Coarasa, Alejandro (Hindawi Publishing Corporation, 2013)
Fast biodegradable (12 h < half-life < 48 h) radioactive labeled microspheres are needed for PET and SPECT lung perfusion and radiomicrosphere therapy planning. An emulsion method was used to create 30.1 ±4.8 μm size range microspheres with biodegradable Chitosan glycol (CHSg). Microspheres were characterized and labeled with (99m)Tc or (68)Ga as an alternative to MAA in perfusion PET and SPECT studies. Surface decoration of CHSg microspheres with p-SCN-Bn-NOTA was performed to increase (68)Ga  in vivo stability. (99m)Tc was labeled directly to the CHSg microspheres. Labeling yield and in vitro radiochemical stability were evaluated. In vitro CHSg microsphere degradation half-life was ~24 hours in porcine blood. Labeled microspheres were injected into Sprague Dawley rats and biodistribution was determined after 2 and 4 hours. Both (99m)Tc-CHSg and (68)Ga-NOTA-CHSg were quickly allocated in the lungs after injection. (99m)Tc-CHSg showed 91.6 ± 6.5% and 83.2 ± 4.1% of the decay corrected injected activity remaining in the lungs after 2 and 4 hours, respectively. For the obtained (68)Ga-NOTA-CHSg microspheres, lung allocation was very high with 98.9 ± 0.2% and 95.6 ± 0.9% after 2 and 4 hours, respectively. The addition of p-SCN-Bn-NOTA acts as a radioprotectant eliminating the released (68)Ga activity from the lungs to the bladder protecting the other organs.